CREATIVE NEEDS IN THE FORMATION OF INNOVATIVE THINKING OF YOUNG PEOPLE AND FACTORS FOR ITS IMPROVEMENT - Abdurakhmanov Hasan Ibragimovich (Journal of Higher Education and Academic Advancement, 2024)
In the formation of a new society in our country, an important foundation is provided by reforms aimed at ensuring its gradual development, consistent material and spiritual potential. Achieving the effectiveness of such large-scale social and cultural activities depends on the knowledge of specialists working in each field. This will largely depend on readiness for spiritual and intellectual renewal. However, we will not be mistaken if we say that such creative activity does not always have a positive meaning when society has entered a new era of social development.